Fintech, financial inclusion and income inequality nexus in Africa - Tough Chinoda; Tafirei Mashamba (Cogent Economics & Finance, 2021)
Financial institutions play a pivotal role in the efficient allocation of capital resources. However, some households and firms may be excluded from formal financial markets due to asymmetric information and market imperfections, thereby adversely affecting equitable income distribution. On the other hand, among other things, access to finance is viewed as one of the key tools to fight poverty. This study develops a novel double FFI Model and applies the structural equation modelling to simultaneously analyze the interaction between financial technology, financial inclusion, and income inequality in a panel of 25 African countries over the periods 2011, 2014, and 2017. The results show that financial inclusion mediates the financial technology-income inequality relationship thus playing a fundamental role in reducing income inequality in Africa. On the policy front, the study urges African policymakers and regulators to craft policies that enhance Fintech developments and financial inclusion.
Keywords: 330; Africa; financial inclusion; Fintech; income inequality; structural equation modelling